2003
DOI: 10.1001/archpedi.157.11.1128
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain in Adult Female Caregivers of Children With Physical Disabilities

Abstract: The prevalence of LBP is higher in caregivers of children needing assistance with transfers. This increased prevalence is associated with the transferability of the child and mood of the caregiver. Results of this study suggest that physical and psychological factors both contribute to the presence of nonoccupational LBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 22 publications
4
52
0
10
Order By: Relevance
“…La percepción subjetiva sobre su estado de salud se ha centrado sobre todo en la existencia de limitaciones físicas por el peso del niño, así como por una mayor sensibilidad a enfermedades, lo que concuerda con estudios como el de Tong y col 24 donde se señalaba la mayor probabilidad de las madres de estos niños de padecer dolores a nivel dorsal.…”
Section: Discussionunclassified
“…La percepción subjetiva sobre su estado de salud se ha centrado sobre todo en la existencia de limitaciones físicas por el peso del niño, así como por una mayor sensibilidad a enfermedades, lo que concuerda con estudios como el de Tong y col 24 donde se señalaba la mayor probabilidad de las madres de estos niños de padecer dolores a nivel dorsal.…”
Section: Discussionunclassified
“…So far, many studies have mainly focused on psychological health of caregivers. Studies of the physical health effects are less conclusive but suggest increased physical vulnerability [54][55][56]. Thus, it is desirable to adhere to a broadly defined HRQoL measure, without eliminating any domains in advance.…”
Section: Discussionmentioning
confidence: 99%
“…37 For example, in 1 study, more than 70% of mothers of children with physical disabilities reported low back pain. 38 When the health of parents or caregivers is compromised, outcomes for their children with CP might suffer. Pediatricians should provide family-centered care for children with CP and their families, because such care reduces stress and enhances parental well-being.…”
Section: Family Supportmentioning
confidence: 99%